Australian atmospheric lead deposition reconstructed using lead concentrations and isotopic compositions of archival lichen and fungi. (January 2016) - Wu, Liqin; Taylor, Mark Patrick; Handley, Heather K.; Wu, Michael
Abstract: Lead concentrations and their isotopic compositions were measured in lichen genera Cladonia and Usnea and fungi genus Trametes from the Greater Sydney region (New South Wales, Australia) that had been collected and archived over the past 120 years. The median lead contents were elevated in lichens and fungi prior to the introduction of leaded petrol ( Cladonia 12.5 mg/kg; Usnea 15.6 mg/kg; Trametes 1.85 mg/kg) corresponding to early industrial development. During the use of leaded petrol for automobiles in Australia from 1932 to 2002, total median lead concentrations rose: Cladonia 18.8 mg/kg; Usnea 21.5 mg/kg; Trametes 4.3 mg/kg. Following the cessation of leaded petrol use, median total lead concentrations decreased sharply in the 2000s: Cladonia 4.8 mg/kg; Usnea 1.7 mg/kg. The lichen and fungi isotopic compositions reveal a significant decrease in 206 Pb/ 207 Pb values from the end of 19th century to the 1970s. The following decades were characterised by lower allowable levels of lead additive in fuel and the introduction of unleaded petrol in 1985. The environmental response to these regulatory changes was that lichen and fungi 206 Pb/ 207 Pb values increased, particularly from 1995 onwards. Although the lead isotope ratios of lichens continued to increase in the 2000s they do not return to pre-leaded petrol values. This demonstrates that historic leaded petrol emissions, inter alia other sources, remain a persistent source of anthropogenic contamination in the Greater Sydney region. Highlights: Total lead and isotopic composition can be measured in historic lichen and fungi. Historic lichen and fungi samples can distinguish polluted and unpolluted areas. Former leaded petrol depositions remain a significant environmental contaminant. Abstract : Analysis of a 120-year record of lichens and fungi from the Greater Sydney basin reveal marked shifts in total lead concentrations and lead isotope ratios in response to geogenic inputs, leaded petrol use and industrial emissions.